2020
DOI: 10.1111/jch.14016
|View full text |Cite
|
Sign up to set email alerts
|

Fixed‐dose combination of amlodipine and atorvastatin improves clinical outcomes in patients with concomitant hypertension and dyslipidemia

Abstract: The combination of certain risk factors such as hypertension and dyslipidemia can act multiplicatively or synergistically to increase the risk of CVD events. 4,5 Additionally, the relationship between these two risk factors is an important modifiable element for CVD. Therefore, this synergistic relationship is recognized by most major clinical guidelines used to aid the management of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Adequate BP and LDL-C control are recommended by clinical guidelines both in primary and secondary CVD prevention [29,35,36]. In our previous study, we only demonstrated the bene cial effect of reducing major adverse cardiovascular events with FDC of amlodipine/atorvastatin in the primary prevention setting [23]. In the present study, we further analyzed the differences in e cacy among three study groups with regards to primary and secondary CVD prevention, and the results were comparable in composite CV outcome.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Adequate BP and LDL-C control are recommended by clinical guidelines both in primary and secondary CVD prevention [29,35,36]. In our previous study, we only demonstrated the bene cial effect of reducing major adverse cardiovascular events with FDC of amlodipine/atorvastatin in the primary prevention setting [23]. In the present study, we further analyzed the differences in e cacy among three study groups with regards to primary and secondary CVD prevention, and the results were comparable in composite CV outcome.…”
Section: Discussionmentioning
confidence: 67%
“…In our previous study, we demonstrated that FDC regimen of amlodipine and atorvastatin improved composite CV outcomes compared to FEC of the same medications in patients with newly diagnosed hypertension and dyslipidemia during a 5-year follow-up period [23]. In that study, the medication adherence as assessed by PDC was better in the FDC than in the FEC group (0.49 ± 0.26 versus 0.32 ± 0.3, P < 0.001), and this may explain the results.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fixed-dose combinations (FDC) contribute to a better clinical outcome with increased compliance over monotherapy [ 1 - 3 ]. In this context, many pharmaceutical companies are interested in the development of FDC.…”
Section: Introductionmentioning
confidence: 99%